if tan A = a tan B and sin A = b sin B prove that cos^2 A = b^2 - 1/ a^2 -1
Answers
Answered by
8
》tanA=a(tanB)
》a=tanA/tanB
》a^2=tan^2A/tan^2B .......(i)
And;
》b=sinA/sinB
》b^2=sin^2A/sin^2B ......(ii)
RHS=b^2-1/a^2-1
=sin^2A-sin^2B/sin^2B×tan^2A-tan^2B/tan^2B
=sin^2A-sin^2B/sin^2B×(sin^2A×cos^2B- sin^2B×cos^2A)/(cos^2A×cos^2B)×(cos^2B /sin^2B)
= cos^2A
HENCE PROVED
》a=tanA/tanB
》a^2=tan^2A/tan^2B .......(i)
And;
》b=sinA/sinB
》b^2=sin^2A/sin^2B ......(ii)
RHS=b^2-1/a^2-1
=sin^2A-sin^2B/sin^2B×tan^2A-tan^2B/tan^2B
=sin^2A-sin^2B/sin^2B×(sin^2A×cos^2B- sin^2B×cos^2A)/(cos^2A×cos^2B)×(cos^2B /sin^2B)
= cos^2A
HENCE PROVED
Answered by
0
Answer:
Proof of the below relation is explained below
Step-by-step explanation:
Given trigonometric relations are
From these two relations,we have
Using trigonometric identity we can write that
From our given relations we have
Substituting these in the above mentioned identity we get,
Therefore,it is proved that
#SPJ2
Similar questions
Political Science,
8 months ago
Science,
8 months ago
English,
8 months ago
English,
1 year ago
Math,
1 year ago